1997
DOI: 10.1007/s001340050339
|View full text |Cite
|
Sign up to set email alerts
|

ARDS caused by herpes simplex virus pneumonia in a patient with Crohn's disease: a case report

Abstract: Pneumonia caused by herpes simplex virus type 1 (HSV1) is rare and occurs in severely immunosuppressed patients. HSV1 can be detected in bronchoalveolar lavage (BAL) from patients presenting with respiratory failure, but its direct effect on disease is difficult to prove. We demonstrate the causative role of HSV1 in the case of a 44-year-old male with Crohn's disease who presented to the intensive care unit with the acute respiratory distress syndrome after surgery. BAL cells were cultured and immunofluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 9 publications
1
13
0
2
Order By: Relevance
“…To date, HSV bronchopneumonitis has mostly been described in patients taking immunosuppressants [20,21], with ARDS [22], after surgery [23][24][25][26], or burn victims [27,28]. It was recently demonstrated that HSV bronchopneumonitis was frequently detected among nonimmunocompromised patients with prolonged mechanical ventilation; in our monocentric study, we found that out of 201 patients suspected of having ventilatorassociated pneumonia (VAP), 42 (21%) were diagnosed with HSV bronchopneumonitis.…”
Section: Herpesviridaementioning
confidence: 83%
“…To date, HSV bronchopneumonitis has mostly been described in patients taking immunosuppressants [20,21], with ARDS [22], after surgery [23][24][25][26], or burn victims [27,28]. It was recently demonstrated that HSV bronchopneumonitis was frequently detected among nonimmunocompromised patients with prolonged mechanical ventilation; in our monocentric study, we found that out of 201 patients suspected of having ventilatorassociated pneumonia (VAP), 42 (21%) were diagnosed with HSV bronchopneumonitis.…”
Section: Herpesviridaementioning
confidence: 83%
“…[2] Invasive HSV infections have also been reported in patients taking azathioprine [57,13] and methotrexate [14] for IBD. Post-marketing surveillance studies of IBD patients receiving newer immunomodulatory therapies (e.g., biologic therapies) less frequently evaluate the specific risk of HSV infections, as compared to herpes zoster, mycobacterial, and fungal infections.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the exact role of HSV in ICU patients, ie, as a marker of disease severity or true pathogen with its own morbidity/mortality, remains unclear. 2,5 To date, HSV BPN has mostly been described in patients taking immunosuppressants, 7,8 with acute respiratory distress syndrome (ARDS), 9 after surgery 10 -13 or in burn victims. 14,15 It has been recently demonstrated that HSV bronchopneumonitis was frequently detected among nonimmunocompromised patients with prolonged mechanical ventilation: in a single center study, Luyt et al found that out of 201 patients suspected of having ventilator-associated pneumonia, 42 (21%) were diagnosed with HSV bronchopneumonitis.…”
Section: Signification Of Viral Reactivationmentioning
confidence: 99%